Pencegahan Tindak Pidana Terorisme di Indonesia melalui Kebijakan Migrasi: Dampak dan Tantangan - A. Taha, Ikram; Jayawardhana, Wilman; Siregar, Parida Johanna; Mustika, Adhista Cahya (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
International migration is carried out by people from various parts of the world with specific aims and objectives. Some people do international migration deliberately to leave their country of origin due to conflicts, natural disasters, repressive governments, economic factors, etc. This study aims to determine the relationship between international migration and acts of terrorism in Indonesia. The research method is a qualitative descriptive analytical method. Acts of terrorism and migration become instruments in understanding and formulating explanations about the relationship between the two. Literature and document searches are used to collect data and information. The results of the study show that migration is one of the factors that encourage acts of terrorism in Indonesia. Actions of deconstruction by the government and cooperation between state institutions are needed to minimize acts of terrorism caused by migration. Keywords: Migration, Refugee, Terorism